1994
DOI: 10.1002/1097-0142(19940415)73:8<2053::aid-cncr2820730807>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Gastric carcinoids. An immunohistochemical and clinicopathologic study of 104 patients

Abstract: Background. Gastric carcinoids are uncommon, and are unlike carcinoids at other gastrointestinal sites, clinically and pathologically. Methods. The authors studied specimens from 104 patients with gastric carcinoid, with study emphasis being placed on pathologic features, immunohistochemistry, clinical associations, and prognostic factors. Results. The average age of the 47 male patients and 57 female patients was 61 years. Twenty‐seven patients had chronic atrophic gastritis, 12 had pernicious anemia, and 6 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…Thomas et al (26) analyzed 104 gastric carcinoids, the majority of which exhibited a diameter of <2.0 cm, and observed that the infiltration depth was restricted 24 (30.8) to the mucosa and submucosa. Soga (27) investigated 1,914 gastrointestinal carcinoids and hypothesized that the diameter of the tumor was closely associated with metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Thomas et al (26) analyzed 104 gastric carcinoids, the majority of which exhibited a diameter of <2.0 cm, and observed that the infiltration depth was restricted 24 (30.8) to the mucosa and submucosa. Soga (27) investigated 1,914 gastrointestinal carcinoids and hypothesized that the diameter of the tumor was closely associated with metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Also, chromogranin and argyrophilic positivity are noticed. 2,11 Immunohistochemistry with chromogranin A (CgA) and synaptophysin assessment is of relevance in identifying hyperplasia, dysplasia and malignant transformation of ECL cells. Also, immunohistochemical determination of the proliferative index with Ki-67 and evaluation of the mitotic index, by counting number of mitosis per 10 high-power fields, are mandatory, with a negative prognostic meaning when Ki-67 is > 2% and mitotic index is > 2.…”
Section: Discussionmentioning
confidence: 99%
“…Up to more than 70% of cases (12,(14)(15)(16)(17)(18)(19) are associated with type-A chronic atrophic gastritis (ACAG) or pernicious anemia (gastric CTs, type 1). They are usually smaller than 1 cm and multifocal in 50%.…”
Section: Discussionmentioning
confidence: 99%
“…When greater than 2 cm these tumors are usually fatal (16). In our series no gastric CT was greater than 20 mm, and most were treated endoscopically (Table III).…”
Section: Discussionmentioning
confidence: 99%